Cost Saving of Stress Ulcer Prophylaxis Used in Non-Intensive Care Unit (ICU) Inpatients - Hening Pratiwi; Laksmi Maharani; Ika Mustikaningtias (MPI (Media Pharmaceutica Indonesiana), 2020)
Stress ulcer prophylaxis (SUP) is largely prescribed to ICU and non-ICU patients. SUP, an acid-suppressive drug, is overused in hospital settings mainly due to inadequate prescriptions in low-risk patients. In this context, the appropriate administration of SUP needs to be analyzed, and the potentially saved money from reducing excessive use can thereby be quantified. This study was intended to calculate potential cost savings in inappropriate SUP therapy in non-ICU inpatients. With a non-experimental retrospective design, it analyzed medical records and details obtained from the financial department of “X” hospital in Purwokerto, Indonesia. The data were collected from 80 non-ICU inpatients in May 2015, which were selected by purposive sampling. We calculated potential cost savings by referring to the American Society of Health-System Pharmacists (ASHP) guidelines that had been modified by Zeitoun (2011) for stress ulcer prophylaxis in non-ICU inpatients. The results showed that inappropriate indications and doses were found in 32.5% and 18% of selected patients, respectively. Before the cost-saving calculation, patients had to spend USD 2,411. However, after the analysis eliminated unnecessary SUP use, this number was proven to be potentially decreased by USD 512 to only USD 1,899. Based on the Wilcoxon Sign Rank Test result (p = 0.000 (≤ 0.05)), there was a significant difference between the total cost before and after the application of modified ASHP guidelines for appropriateness. After a thorough assessment, we concluded that the treatment cost could be reduced by identifying and excluding inappropriateness in SUP therapy.